Copper defects and conductivity in Bi-Pb-Sr-Ca-Cu-O glasses - Guskos, N.; Gazda, M.; Typek, J.; V. Likodimos; Wabia, M.; Fuks, H.; Sadowski, W. (Radiation Effects and Defects in Solids, 2003)
Glass ceramics of the composition (Bi0.8Pb0.2) 4Sr3Ca3Cu4O8 prepared by the melt quenching technique and the crystalline phases produced by the rapid thermal annealing have been studied by electrical resistivity and electron paramagnetic resonance (EPR) measurements in the temperature range from liquid helium up to room temperature. The concentration of the EPR active Cu 2+ paramagnetic centers decreases as conductivity increases for the glass ceramics and disappears alter crystallization and the growth of superconducting phases, similar to bulk high-Tc,. superconductors. The EPR spectra of both glass and crystallized ceramics after short-time annealing indicate the coexistence of Cu2+ paramagnetic ions and the exchange coupled clusters.
cited By 0